Chemistry and Kinetics of Oxidative Sulphuric Acid Leaching of Cobalt-Bearing Convener Slags - S. I. Sobol (The Minerals, Metals and Materials Society, 1993)
Completeness of cobalt recovery from slag requires decomposition of maggemite and non - ferrous metal desorption with polymerized silicon-acid. Cobalt losses are reduced in leaching tai1s up to 200 g/t of iron.